2011
DOI: 10.3917/machr.209.0043
|View full text |Cite
|
Sign up to set email alerts
|

Transition démocratique et reporting environnemental, social et de gouvernance (ESG) en Tunisie

Abstract: L’objectif de cette recherche est d’évaluer si les banques tunisiennes intègrent les nouvelles dimensions de la performance : environnementale, sociale et de gouvernance (ESG), comment elles le font et quelles sont les logiques d’appropriation de ces normes internationales. Existe-t-il un lien entre la démocratie et l’ESG ? Les exigences de transparence de l’information, du fameux « rendre compte », de l’accès à l’information, de la prise en compte des responsabilités environnementales, des modalités de contrô… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Tunisia has not yet entered the era of SRI. However, in this country, ESG has started to become a growing concern (Ben Rhouma et al, 2011). Several reforms have been initiated in favor of CSR.…”
Section: Introductionmentioning
confidence: 99%
“…Tunisia has not yet entered the era of SRI. However, in this country, ESG has started to become a growing concern (Ben Rhouma et al, 2011). Several reforms have been initiated in favor of CSR.…”
Section: Introductionmentioning
confidence: 99%
“…Chakroun (2012) showed that voluntary disclosure policy in annual reports of Tunisian firms is seen by analysts as being minimalist. Recently, the ESG started becoming a growing concern (Ben Rhouma et al, 2011). The many reforms initiated in the favor of CSR constitute a real incentive to the commitment by companies in a socially responsible approach.…”
Section: Introductionmentioning
confidence: 99%